Efficacy and Safety of Ertugliflozin in Type 2 Diabetes: A Systematic Review and Meta-Analysis - Liu, Li; Shi, Fang-Hong; Xu, Hua; Wu, Yue; Gu, Zhi-Chun; Lin, Hou-Wen (Frontiers in Pharmacology, 2022)
Abstract Objective: To evaluate the efficacy and safety of ertugliflozin in patients with type 2 diabetes. Methods: MEDLINE, EMBASE, and Cochrane Library were searched (31 July 2021) for phase II/III randomised clinical trials, which reported the efficacy and safety of ertugliflozin. Continuous variables were calculated as weighted mean difference (WMD) and associated 95% confidence intervals (CIs); dichotomous data were expressed as risk ratios (RRs) with 95% CIs. Results: Nine randomised clinical trials including 5638 type 2 diabetes patients were included. For efficacy, ertugliflozin significantly reduced HbA1c (%) (WMD −0.452%; 95% CI −0.774 to −0.129), fasting plasma glucose (FPG) (WMD −0.870 mmol/L; 95% CI −1.418 to −0.322), body weight (WMD −1.774 kg; 95% CI −2.601 to −0.946), and blood pressure levels (systolic blood pressure: WMD −2.572 mmHg; 95% CI −3.573 to −1.571 and diastolic blood pressure: WMD −1.152 mmHg; 95% CI −2.002 to −0.303) compared with placebo and other hypoglycaemic agents. Compared with placebo, ertugliflozin was superior in reducing HbA1c (%) (WMD −0.641%) and FPG (WMD −1.249 mmol/L). And compared with active agents, ertugliflozin also could decrease HbA1c by 0.215% and FPG by 0.266 mmol/L. The interactive effect between different controls was significant (P interaction of 0.039). For safety, similar to other sodium-glucose cotransporter type-2 inhibitors, ertugliflozin mainly increased the risk of genital mycotic infection (RR: 4.004; 95% CI 2.504 to 6.402). There was no significant difference in the incidence of any AEs, AEs related to study drug, serious AEs, deaths, and discontinuations due to AEs. Results were consistent with the most primary outcomes in subgroups analysis and sensitivity analysis. Conclusion: Ertugliflozin was relatively effective and tolerated in patients with type 2 diabetes compared with placebo or other hypoglycaemic agents, except for a high risk of genital mycotic infection.